2011
DOI: 10.1186/1471-2407-11-149
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic antiproliferation effect of curcumin and docosahexaenoic acid in SK-BR-3 breast cancer cells: unique signaling not explained by the effects of either compound alone

Abstract: BackgroundBreast cancer is a collection of diseases in which molecular phenotypes can act as both indicators and mediators of therapeutic strategy. Therefore, candidate therapeutics must be assessed in the context of multiple cell lines with known molecular phenotypes. Docosahexaenoic acid (DHA) and curcumin (CCM) are dietary compounds known to antagonize breast cancer cell proliferation. We report that these compounds in combination exert a variable antiproliferative effect across multiple breast cell lines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 76 publications
1
53
0
2
Order By: Relevance
“…Moreover, curcumin is known to modulate DNA methylation in colorectal cancer cells (122), and recent advances in microarray and sequencing technologies have reported miRNA genes that are silenced by methylation in cancer (126). It has also been suggested that DHA enhances cell permissiveness to curcumin uptake (4, 137). Therefore, a diet containing both n-3 PUFA and curcumin may suppress colon cancer by acting on different molecular targets.…”
Section: Effects Of N-3 Pufa Fiber and Curcumin On Noncoding Micrornasmentioning
confidence: 99%
“…Moreover, curcumin is known to modulate DNA methylation in colorectal cancer cells (122), and recent advances in microarray and sequencing technologies have reported miRNA genes that are silenced by methylation in cancer (126). It has also been suggested that DHA enhances cell permissiveness to curcumin uptake (4, 137). Therefore, a diet containing both n-3 PUFA and curcumin may suppress colon cancer by acting on different molecular targets.…”
Section: Effects Of N-3 Pufa Fiber and Curcumin On Noncoding Micrornasmentioning
confidence: 99%
“…It is an anti-inflammatory agent and can sensitize existing chemotherapies. This synergism is likely due to its concomitant effect on both COX and LOX enzymes as well as cPLA2 phosphorylation, which has been described [158160]. While curcumin can be consumed in great quantity without adverse effect, its bioavailability is limited [161].…”
Section: Targeting Lipid Pathwaysmentioning
confidence: 99%
“…Subsequently DHA was shown to target SOD1 in a PPARalpha dependent manner [201]. DHA also synergizes with and enhances curcumin activity against breast cancer cell proliferation [158]. …”
Section: Targeting Lipid Pathwaysmentioning
confidence: 99%
“…It is found in the rhizome of the herb Curcuma longa Linn., which is commonly known as turmeric. 1 Turmeric is widely used in therapeutic preparations against anorexia, rhinitis, herpes zoster, acne, cough, urinary tract diseases, diabetic wounds, hepatic disorder, rheumatism and sinusitis. [1][2][3] Curcumin has several properties including antioxidant, antimicrobial, anti-inflammatory, antiviral, anti-carcinogenic and anti-diabetic activities.…”
Section: Introductionmentioning
confidence: 99%
“…1 Turmeric is widely used in therapeutic preparations against anorexia, rhinitis, herpes zoster, acne, cough, urinary tract diseases, diabetic wounds, hepatic disorder, rheumatism and sinusitis. [1][2][3] Curcumin has several properties including antioxidant, antimicrobial, anti-inflammatory, antiviral, anti-carcinogenic and anti-diabetic activities. [4][5][6][7][8][9] Recent studies have shown that curcumin also suppresses neuropathic pain induced by chronic sciatic nerve ligation.…”
Section: Introductionmentioning
confidence: 99%